Adjustments, roles, and types of support received by widowed Filipino elderly living in their children's homes - Barretto, Pearl Stephanie C.; Panagsagan, Marie Ysabel Q.; Agustin, Estrella R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT This paper aims to determine and describe the widowed Filipino elderly's adjustment, roles, and types of support received upon moving in with their child after being widowed. Six case studies were conducted via semi-structured interviews as well as four hours worth of observation. The participants were determined through purposive sampling and their ages ranged from 66 to 82 years old. Results showed that the elderly go through adjustments in restriction of time or activities, food, and role change upon moving in with their child. The roles they assumed upon moving in with their children were categorized into supervisory and domestic roles. Lastly, the types of support they receive from their children are composed of material, financial and material, and social support.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Aging parents -- Philippines; Widows -- Philippines